Analysis of precipitation extremes based on satellite and high-resolution gridded data set over Mediterranean basin - Nastos, P. T.; Kapsomenakis, J.; Douvis, K. C. (Atmospheric Research, 2013)
The objective of this study is to compare and analyze satellite precipitation extremes of Tropical Rainfall Measuring Mission level 3 output (TRMM 3B42) over Mediterranean region against the respective high resolution gridded precipitation datasets (0.25. ×. 0.25) based on the E-OBS project, for the period 2000-2011.The Tropical Rainfall Measuring Mission (TRMM) is a joint U.S.-Japan satellite mission to monitor tropical and subtropical precipitation and to estimate its associated latent heating. The E-OBS data set (a European daily high-resolution gridded dataset of surface temperature and precipitation) was developed as part of the European Union Framework 6 ENSEMBLES project, with the aim being to use it for validation of Regional Climate Models (RCMs) and for climate change studies.The indices used in the analysis can be divided in three categories: percentile, absolute and duration indices. The percentile indices concern: very wet days (the number of days with daily precipitation amount above the 95th percentile from the examined period) and extremely wet days (the number of days with daily precipitation amount above the 99th percentile from the examined period). The absolute threshold indices concern: number of heavy precipitation days (number of days with daily precipitation amount above 10. mm), number of very heavy precipitation days (number of days with daily precipitation amount above 20. mm) and simple daily intensity index (daily precipitation amount on wet days in a period per number of wet days in the period). The duration indices concern consecutive dry days (the largest number of consecutive days with daily precipitation amount below 1. mm) and consecutive wet days (the largest number of consecutive days with daily precipitation amount above 1. mm).The spatial distribution of the differences between the two datasets along with the spatial distribution of the correlation coefficients are presented and analyzed. Results show considerable regional differences of precipitation indices over the Mediterranean Region. © 2013 Elsevier B.V.
Keywords: Atmospheric temperature; Climate change; Correlation coefficient; data set; E-OBS; Extreme precipitation; Extreme precipitation indices; latent heat flux; Mediterranean; Mediterranean Sea; Precipitation (meteorology); precipitation assessment; Rain gages; Regional climate models; satellite data; Satellite precipitation; Satellites; Spatial distribution; threshold; TRMM; Tropical rainfall measuring missions